Comparison between May‐Grünwald‐Giemsa and rapid cytological stains in fine‐needle aspirates of canine mast cell tumour: Diagnostic and prognostic implications. (1st July 2018) - Sabattini, S.; Renzi, A.; Marconato, L.; Militerno, G.; Agnoli, C.; Barbiero, L.; Rigillo, A.; Capitani, O.; Tinto, D.; Bettini, G.
Abstract : Mast cell tumours (MCTs) are often diagnosed by cytology based on the identification of purple intracytoplasmic granules with methanolic Romanowsky stains, including May‐Grünwald‐Giemsa (MGG). In clinical practice, aqueous rapid stains (RS) are commonly used, but mast cell granules may not stain properly. Aim of this prospective study was to investigate the frequency of MCT hypogranularity with RS and its potential implications in tumour identification, cytological grading assessment and recognition of nodal metastatic disease. Cytological preparations of canine primary MCTs and metastatic lymph nodes with subsequent histopathological confirmation were included. For each case, good‐quality smears were stained with both MGG and RS and comparatively assessed. Eleven of 60 (18.3%) primary MCTs were hypogranular with RS; 9 of them were histologically high‐grade tumours and in 3 cases (5%) a definitive MCT diagnosis could not be made. Accuracy in cytological grading assessment (85%) did not differ between RS and MGG. Thirteen of 28 (46.4%) metastatic lymph nodes were hypogranular with RS and 3 independent observers failed to identify nodal MCT metastases in 7% to 18% of RS‐stained smears. This study confirms that, in limited cases, RS can be ineffective in staining MCT granules, particularly in high‐grade tumours, thus making diagnosis more dependent on experience and quality of preparations. In dubious cases, methanolic stains should be applied. The use of RS is discouraged for the search of nodal metastases, as the identification of isolated mast cells can be more challenging.